Study on the adhesion performance of basalt fiber and polypropylene fiber based on unified phase-field theory and cohesive zone model - Zhao Wen; Wang Simeng; Wang Huiming; Cai Guanghui (PLoS ONE, 2026)
In recent years, mixing an appropriate amount of flexible fibers(e.g., basalt fibers, polypropylene fibers, etc.) into concrete has become a common practice. Numerous engineering applications have shown that adding one or more types of flexible fibers not only significantly enhances the mechanical properties of concrete, such as flexural and tensile strength, but also markedly improves its durability by resisting sulfate and chloride ion attack and reducing crack formation. Building upon this practical significance, this study developed finite element models to investigate the pull-out behavior of basalt fibers and polypropylene fibers based on the unified phase-field theory (UPFT) coupled with the cohesive zone model (CZM). The fiber-matrix interfacial adhesion was simulated using zero-thickness cohesive elements to investigate and analyze the adhesion performance of the two fiber types pulled out from the concrete matrix. A series of numerical simulations was conducted to evaluate the effects of embedment depth, fiber diameter, and interfacial properties on the mechanical response. The predicted pull-out loads exhibited good agreement with experimental results, confirming the reliability and accuracy of the proposed modeling framework. The findings indicate that the peak pull-out load of both basalt and polypropylene fibers increases with greater embedment depth and larger fiber diameter. Furthermore, enhancing either the interfacial adhesion strength or the matrix strength significantly improves the reinforcing effectiveness of the fibers within the concrete matrix.